Malignancy risk in AUS thyroid lesions: comparison between FNA and CNB with implications for NIFTP diagnosis - Kim, Yeseul; Shin, Jae Ho; Sung, You-Na; Park, Dawon; Oh, Harim; Ryu, Hyo Seon; Kim, Kyeong Jin; Kim, Hyun Joo; Kim, Sin Gon; Kim, Hoon Yub; Jung, Kwang Yoon; Baek, Seung-Kuk; et al. (Frontiers in Endocrinology, 2025)
BackgroundWe aimed to evaluate and compare the efficacies and roles of core-needle biopsy (CNB) and repeat fine-needle aspiration (rFNA) in diagnosing thyroid nodules initially diagnosed as atypia of undetermined significance (AUS) by FNA. Additionally, we aimed to investigate the potential of CNB in diagnosing non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) and other follicular neoplasms (FNs), addressing its advantages over FNA in overcoming the diagnostic limitations of FNA.MethodsOverall, 635 nodules (7.3%) initially diagnosed as AUS were retrospectively reviewed from among 8,670 thyroid FNAs that were performed between 2018 and 2021. Malignancy rates were calculated as upper and lower limit estimates. rFNA was performed on 315 AUS nodules, and CNB was conducted on 62 patients.ResultsComparing the outcomes, CNB showed significantly fewer non-diagnostic results than rFNA (0% vs. 44.4%, p = 0.008) and a higher rate of FN diagnosis (11.3% vs. 0.3%, p < 0.001). In the AUS category, CNB demonstrated higher diagnostic rates for FNs, including NIFTP and follicular variant papillary thyroid carcinoma (50% vs. 18%). CNB significantly reduced the rate of insufficient diagnoses and increased the rate of diagnosing FNs. Moreover, CNB proved more effective than rFNA in diagnosing FNs, including NIFTP, within the AUS category, ensuring accurate detection without underdiagnosis.ConclusionCNB may serve as a more reliable diagnostic tool for cases initially classified as AUS, particularly when repeat insufficient results are obtained or when diagnosing FNs and NIFTP.